PENGARUH BEBAN PAJAK TANGGUHAN, PERENCANAAN PAJAK DAN DEBT TO EQUITY RATIO TERHADAP PRAKTIK MANAJEMEN LABA - Syilvia Syilvia; Puspahadi Boenjamin; Susi Dwi Mulyani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
The purpose of this research is to identifi, the effect of deffered tax expense, tax planning, and debt to equity ratio to the earnings management practices go public's manufacturing companies. The data used in this research is secondary data datained from financial statements of go public companies in Indonesia Stock Exchange during 2012-2014. The research sample using 57 manufacturing companies each year. The sampling method used is purposive sampling. data analysis method used is quantitative method with descriptive statistics, classic assumptions test and hypothesis test to ident6 independent variables that influence the dependent variable. The result showed that debt to equity ratio has an influence signifikan and positif on earnings management practices. The deferred tax expense has no influence signifikan and positif on earnings management practices. Tax planning no influence signifikan and negatif on earnings management practices.